Green Business Practices and Consumer Behavior in Jambi, Indonesia: An Empirical Investigation - Silvia Jesika; Widya Pratiwi; Syah Amin Albadry; Sasmita Rusnaini; Hamirul (Enigma in Economics, 2024)
The global shift towards sustainability has led to a growing interest in green business practices. This study aims to investigate the influence of green business practices on consumer behavior in the context of Jambi, Indonesia. A quantitative research approach was employed, utilizing a structured questionnaire to collect data from a sample of 350 consumers in Jambi. Data analysis involved descriptive statistics, correlation analysis, and multiple regression analysis. The findings revealed a positive correlation between green business practices and consumer behavior. Specifically, factors such as eco-labeling, green product offerings, and corporate social responsibility initiatives were found to significantly influence consumer purchase intentions and brand loyalty. In conclusion, this study contributes to the understanding of the relationship between green business practices and consumer behavior in an emerging market context. The results highlight the importance of adopting sustainable practices for businesses seeking to appeal to environmentally conscious consumers in Jambi.